2019
DOI: 10.1186/s40902-019-0222-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lingual nerve injuries in removal of mandibular third molars: a retrospective case-control study

Abstract: Background Through the analysis of clinical data, we attempted to investigate the etiology and determine the risk of severe iatrogenic lingual nerve injuries in the removal of the mandibular third molar. Methods A retrospective chart review was performed for patients who had undergone microsurgical repair of lingual nerve injuries. The following data were collected and analyzed: patient sex, age, nerve injury side, type of impaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…In total, 1063 articles were initially included, comprising 1023 from electronic searches and 2 from other resources; 625 records were retained after duplicates were removed. We screened the 625 articles and finally found 40 articles [ 4 , 5 , 6 , 8 , 9 , 11 , 15 , 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] for further assessment. We assessed 40 articles [ 4 , 5 , 6 , 8 , 9 , 11 , 15 , 16 , 20 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 1063 articles were initially included, comprising 1023 from electronic searches and 2 from other resources; 625 records were retained after duplicates were removed. We screened the 625 articles and finally found 40 articles [ 4 , 5 , 6 , 8 , 9 , 11 , 15 , 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] for further assessment. We assessed 40 articles [ 4 , 5 , 6 , 8 , 9 , 11 , 15 , 16 , 20 ,…”
Section: Resultsmentioning
confidence: 99%
“…We screened the 625 articles and finally found 40 articles [ 4 , 5 , 6 , 8 , 9 , 11 , 15 , 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] for further assessment. We assessed 40 articles [ 4 , 5 , 6 , 8 , 9 , 11 , 15 , 16 , 20 , 21 , 22 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the previous studies, the injured lingual nerve is usually not supported by a bony canal while inferior alveolar nerve runs within the canal. Thus, the recovery of IANI is relatively quick while the recovery of an injured lingual nerve is relatively slower than that for the IAN (Loescher, Smith, & Robinson, 2003; Tojyo et al., 2019). In addition, previous studies revealed that the lingual nerve has fewer fascicles with thicker perineurium than the inferior alveolar nerve (Graff‐Radford & Evans, 2003; Tan, Andrawos, Ghabriel, & Townsend, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of lingual nerve injury was found to be highest in females ranging from 30-50 years having distoangular impaction. 15 The use of a dentopanoramic tomography [DPT] or a cone-beam computed tomography [CBCT] is improvised in the preoperative assessment relationship between the inferior dental nerve and mandibular third molar. 15 [ Figure 2-4] Inferior dental nerve injury has been reported to have an incidence 0.41 to 8.1% with temporary damage and incidence Iatrogenic injuries could possibly be due to crushing of tissues while elevating the involved tooth.…”
Section: Neurological Complicationsmentioning
confidence: 99%